Comparative Advantage Under Monopoly: A Note On the Role of Market Power - Emanuele Bacchiega (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We argue that it is the number of agents holding market power, rather than the presence of market power itself, that may force Ricardian economies into autarchy. We apply the concepts of monopoly equilibrium by Baldwin (1948) to the model of Cordella and Gabszewicz (1997) to show that, differently from the oligopoly case, trade always arises at a monopoly equilibrium whereas autarchy is never an outcome. As a consequence, monopoly Pareto-dominates oligopoly.
Keywords: F10; D42; 330